An intracellular adrenomedullin system reduces IL-6 release via a NF-kB-mediated, cAMP-independent transcriptional mechanism in rat thymic epithelial cells. (December 2016) - Castellani, Giulia; Paliuri, Giovanna; Orso, Genny; Paccagnella, Nicola; D'Amore, Claudio; Facci, Laura; Cima, Francesca; Caicci, Federico; Palatini, Pietro; Bova, Sergio; De Martin, Sara
Graphical Abstract: Highlights: Adult rat thymus is a reliable model to study the function of thymic ADM system. ADM inhibits the canonical NF-kB pathway by acting at the transcriptional level. ADM reduces IL-6 production by TECs and may participate to the regulation of Th17/Treg ratio. Abstract: Thymic epithelial cells (TECs) play a key role in the regulation of central immune tolerance by expressing autoantigens and eliminating self-reactive T cells. In a previous paper we reported that adrenomedullin (ADM) and its co-receptor protein RAMP2 are located intracellularly in newborn human thymic epithelial cells (TECs). This work has two main aims: (1) to examine the cellular localization of ADM and its receptor in TECs of adult Wistar rats to validate this animal model for the study of the ADM system and its function(s) in thymus; (2) to investigate the potential modulating effect of ADM on the NF-kB pathway, which is involved through the production of cytokines such as IL-6, in the maturation of T-lymphocytes and immunological tolerance. Our results show that, similarly to human newborn TECs, ADM is localized to the cytoplasm of adult rat TECs, and RAMP2 is expressed in the nucleus but not in the plasma membrane. Pretreatment of TECs for 4 h with ADM significantly reduced lipopolysaccharide (LPS)-induced release of IL-6 (P < 0.001) and expression of the p65 subunit of NF-kB, while doubled the expression of IkBα (P < 0.001), the physiological inhibitor of NF-kB nuclear translocation. These effects were not mediated by activation of the cAMP pathway, a signalling cascade that is rapidly activated by ADM in cells that express plasma membrane RAMP2, but were the consequence of a reduction in the transcription of p65 (P < 0.001) and an increase in the transcription of IkBα (P < 0.05). On the basis of these findings we propose that in rat TECs ADM reduces IL-6 secretion by modulating NF-kB genes transcription through an interaction with a receptor localized to the nucleus. This may partly explain the protective effects of ADM in autoimmune diseases and points to the ADM system of TECs as a novel potential target for immunomodulating drugs.